Innovative solutions for access control management - Malik, Ahmad Kamran 1973-; Anjum, Adeel 1982-; Raza, Basit, 1976- (Advances in information security, privacy, and ethics (AISPE) book series, 2016)
This book features a comprehensive discussion on the trending topics and emergent research in IT security and governance, highlighting theoretical frameworks and best practices, as well as challenges and solutions within the topic of access control and management